Estudio de los restos de un esqueleto de oso pardo procedente de la sima Alberich (Palencia) - Torres Pérez-Hidalgo, Trinidad José; Ortiz Menéndez, José Eugenio; Sánchez-Palencia González, Yolanda; Alcalde, G. (E.T.S.I de Minas y Energía, 2014)
Este trabajo recoge aspectos métricos y morfológicos de un individuo juvenil de Ursus arctos Linneo, procedente de Sima Alberich (Palencia). La datación por racemización de aminoácidos lo sitúa en la glaciación Würm o MIS4. ABSTRACT This paper studies the metrical and morphological characteristics of the skeleton of a young Ursus arctos Linnaeus individual found in a karst shaft (Sima Alberich) in the province of Palencia. Amino acid racemization dating proved that this species inhabited the Iberian Peninsula at the time of the Würm glaciation.